Neuropsychology for occupational therapists : cognition in occupational performance / / edited by Linda Maskill, Stephanie Tempest. - Maskill, Linda, 1959-; Tempest, Stephanie, 1975-; Grieve, June I. (Hoboken, NJ, USA : Wiley Blackwell, 2017)
Providing an accessible introduction to key theories, this title describes cognitive dysfunctions and their effects upon daily life, detailing assessment methodologies and tools along with considerations for interventions. Neuropsychology for Occupational Therapists is a bestselling, comprehensive guide to the assessment and rehabilitation of impaired cognitive function and brain damage. Divided into two parts, the first introduces the fundamental role cognition has in occupational performance, before moving on to examine the theoretical frameworks behind cognitive rehabilitation. The second part covers the key components of each cognitive function, including attention, visual perception, movement, memory, and executive functions, and the disorders associated with them. Revised throughout, this invaluable new edition includes: Updated theory and evidence base of neuropsychology Frameworks and guidelines for assessment and intervention in practice Updated content on attention, memory and executive functions A new chapter on cognitive function in later years, and working with people to maintain cognitive health. Written in a clear and engaging style by an experienced author team of academic occupational therapists, with contributions from expert practising clinicians, it is full of a range of learning features, including case studies, summaries, and reflective activities, as well as for the first time narratives of the lived experience of cognitive impairment. Neuropsychology for Occupational Therapists is essential reading for students, newly qualified practitioners, and all those who work within neuropsychology and cognitive rehabilitation.
Cognition and the Occupational Therapy Process. Occupation and Cognitive Rehabilitation / Stephanie Tempest, Linda Maskill -- Assessment and Measuring Change / Linda Maskill, Stephanie Tempest -- Intervention for Cognitive Impairments and Evaluating Outcomes / Linda Maskill, Stephanie Tempest -- Cognition: Understanding Function and Working with People with Impairments. Cognition: Methods and Processes / Linda Maskill, Stephanie Tempest -- Attention / Richard Jefferson, Linda Maskill -- Visual Perception, Recognition and Agnosia / Linda Maskill, June Grieve -- Complex Perceptual Functions: Body Scheme and Agnosia, Constructional Skills and Neglect / Stephanie Tempest, Linda Maskill -- Memory / Tess Baird, Linda Maskill -- Purposeful Movement and Apraxia / Stephanie Tempest -- Executive Functions / Sacha Hildebrandt -- Cognitive Function in the General Population / Linda Maskill.
Preceded by Neuropsychology for occupational therapists / June Grieve, Linda Gnanasekaran. 3rd ed. 2008.
Includes bibliographical references and index.
Print version record.
Keywords: Clinical neuropsychology; Cognition disorders -- Patients -- Rehabilitation; Occupational therapy; Neuropsychology -- methods; Occupational Therapy -- methods; Neurocognitive Disorders -- diagnosis; Perception -- physiology; Memory Disorders -- diagnosis; Motor Skills Disorders -- diagnosis; Neurologic Examination; Electronic books